Study on the Correlation of CPT value to Soil Parameters - Abigail Anggie Putriana Onggosandojo; Tri Harianto; Sitti Hijraini Nur (Lowland Technology International, 2021)
Soil is one of the factors that has the most important role because it bears the burden of all the constructions that stand on it. Based on this very important role of soil, prior to the start of construction in a location, a soil investigation must be carried out first to find out the condition of the subgrade at the construction site. One of the most frequently used soil investigation methods is Cone Penetration Test (CPT). The purpose of this study includes two things, namely to determine the soil profile at the CPT test location, and to determine the correlation between the data from the Cone Penetration Test results with soil parameters (Soil Volume Weight, Cohesion, and Internal Shear Angle). The method used in this study is to analyze the data from the Cone Penetration Test using the results of the research that has been carried out as a basis for determining the soil profile and the required soil parameters. The results obtained are, the first is based on the data plot on the soil type graph at the Cone Penetration Test (CPT) test location spread over 4 zones, namely Zone 3, Zone 4, Zone 5, and Zone 6. The second is the correlation between soil unit weight and Conus Resistance values are directly proportional, as are Cohesion and friction angles. In addition, the equations used in this paper cannot be used as the main reference, but only used to predict soil parameters when in the field